"Unequal Pay for Equal Work": Why Women Still Lag Behind After the 50th Anniversary of the U.S. Equal Pay Act. (July 2013) - Stanberry, Kurt; Aven, Forrest
The purpose of this article is to demonstrate, through the use of empirical evidence, the continued existence of gender-based compensation inequities in the United States. This is confirmed in an analysis of data collected by the authors showing women workers are paid less than men even when holding jobs with the same titles. Similar findings have been reported in a number of other recent studies. There appears to be grounds to conclude that the difference in pay cannot be totally and satisfactorily explained by factors such as experience or education. While inequities exist, whether continued paycheck inequality proves intentional discrimination remains unclear. However, to address the problem, remedial action is recommended in the form of the passage of new statutory law and the expansion of existing common law.